2020
DOI: 10.3390/ijms21238899
|View full text |Cite
|
Sign up to set email alerts
|

A Budding Relationship: Bacterial Extracellular Vesicles in the Microbiota-Gut-Brain Axis

Abstract: The discovery of the microbiota-gut-brain axis has revolutionized our understanding of systemic influences on brain function and may lead to novel therapeutic approaches to neurodevelopmental and mood disorders. A parallel revolution has occurred in the field of intercellular communication, with the realization that endosomes, and other extracellular vesicles, rival the endocrine system as regulators of distant tissues. These two paradigms shifting developments come together in recent observations that bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 171 publications
(148 reference statements)
0
53
0
Order By: Relevance
“…Additionally, they can communicate with the host through microbe- and pathogen-associated molecular patterns (MAMP and PAMP, respectively), leading to an immunomodulatory action. The GM is a good source of EVs that move beyond the intestine and disseminate to other organs and tissues [ 44 , 99 ]. Furthermore, host cells also secrete EVs and recent evidence suggests that they could also play a role in the development and progression of T1D and T2D [ 100 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they can communicate with the host through microbe- and pathogen-associated molecular patterns (MAMP and PAMP, respectively), leading to an immunomodulatory action. The GM is a good source of EVs that move beyond the intestine and disseminate to other organs and tissues [ 44 , 99 ]. Furthermore, host cells also secrete EVs and recent evidence suggests that they could also play a role in the development and progression of T1D and T2D [ 100 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…The GM is probably the major source of postbiotic constituents. Our resident microbes release a myriad of products, including metabolites and also cell components (reviewed in detail in [ 43 ]), that behave as messengers in the microbiota–host interactions and are of major significance to the host [ 44 , 45 ]. In the present review, however, we focus on the potential of exogenous factors that are orally administered.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gut microbiota can themselves release metabolites including neurotransmitters such as serotonin, dopamine, noradrenaline and GABA. These neurotransmitters and their precursors, hormone-like metabolites and short-chain fatty acids can travel through the circulation to the brain where they can act on respective receptors modulating neuronal and microglial functions [35]. In this gut-brain communication, endocrine pathways also participate such as enteroendocrine cells and the hypothalamic-pituitary-adrenal axis.…”
Section: Gut Microbiota and Brain Communicationmentioning
confidence: 99%
“…Similarly, we have previously shown that the gram-positive bacterium Lacticaseibacillus rhamnosus JB-1 (JB-1; recently reclassified from Lactobacillus 15 and previously misclassified as L. reuteri 16 ) and its MV can promote the number and functions of regulatory T cells, activate TLR2, and induce an immunoregulatory phenotype in dendritic cells (DCs) 17 19 . Substantial evidence now exists that MV from beneficial bacteria can independently influence the host 20 , though their mechanisms of action in many cases remain unclear.…”
Section: Introductionmentioning
confidence: 99%